Modified Basalt with Completed Polyvinyl Chloride Physical-Mechanical Analysis of Samples Based on Their Composition - Adkham, Jumaeva Anora; Fakhriddin, Dostmuradova Mamura (Indonesian Journal Publisher, 2024)
Structure, physical-mechanical, technological properties of plasticized and non-plasticized polymer materials based on PVC composition filled with modified basalt Several methods and relevant information on the obtained results have been described in previously published scientific articles on detection. In addition to these data, it can be noted that any added filler has its effect on physical and mechanical indicators. This study aims to modify basalt with polyvinyl chloride (PVC) and analyze the impact of this modification on the physical and mechanical properties of the resulting composite. The goal is to develop new composite materials that leverage the strengths of both components for superior industrial applications. The research involved literature review, synthesis of basalt fibers, modification with PVC, preparation of composite samples, and physical and mechanical testing. Analyzed parameters included tensile strength, elongation at break, Young's modulus, and stress at break. The research was conducted in the laboratories of the Karshi Engineering-Economics Institute. The results showed that increasing the amount of basalt filler in the PVC composite improved its physical and mechanical properties. Tensile strength and elongation at break significantly increased with higher basalt content. For example, the maximum tensile strength for the composite with 4% basalt was 6.28 MPa, higher than the composite without basalt. Additionally, the relative elongation decreased with increasing basalt content, indicating increased material stiffness. Modifying basalt with PVC resulted in composite materials with enhanced mechanical properties, including improved tensile strength and thermal and chemical resistance. These findings highlight the significant potential of basalt-PVC composites for industrial applications requiring high-performance, durable, and cost-effective materials. Future research could explore the effects of different PVC ratios and types, as well as the impact of additional fillers on composite performance.